International Students’ Perceptions of Service Quality in the UK Banking Sector: An Exploratory Study - Bond, Christopher; Hsu, Marc Ting-Chun (Journal of International Students, 2011)
This study reviews and evaluates international students’ perceptions of UK banks. The specific research objectives were to identify international students’ expectations and perceptions of service quality from UK banks and to assess the quality GAP or dissonance between these. A total of 297 international students studying in the UK responded to the survey. Data gathered was analyzed using Statistical Package for the Social Sciences (SPSS 16). The study reveals that the main areas of service quality with which international students are generally satisfied relates to tangibles such as physical layout and appearance. The key areas of dissatisfaction that the study identified were with factors related to reliability and empathy. This appears to be the first study in the UK banking sector that has focused on service quality with respect to international students.